Anurofauna e cavernas neotropicais: fatores bióticos e abióticos que modulam a ocupação do habitat subterrâneo - Sperandei, Vinícius da Fontoura (Universidade Federal de São Carlos, 2024)
Caves form a network of spaces between rocks, ranging from tiny spaces like crevices to large spaces accessible to humans. This environment has unique characteristics compared to the surface, such as the absence of light, energy supply originating from the epigean environment, mild temperature, and relative humidity tending towards saturation. Among vertebrate animals that live inside natural cavities in Brazilian neotropical regions, anurans still form a taxonomic group with limited scientific framework, and their occupation of the environment is still considered accidental or temporary. The objective is to identify the panorama of cave occupation by anurans, conducting a survey of scientific records and using it to compile a species list. From the records, categorical variables of abiotic nature were extracted, discussing the cave conditions that influence the presence of anurans, as well as biological variables related to home range, natural history, and conservation profile of species recorded in caves. Eighteen scientific publications were found over 42 years with records of anurans in caves, totaling 247 independent records. The species list includes 54 records up to the specific epithet (83 morphotypes), with emphasis on the families Leptodactylidae (13 species), Hylidae (12), and Bufonidae (10) as the richest, predominantly recorded in Minas Gerais and São Paulo, in the Atlantic Forest biome and ecotonal zones between the Atlantic Forest and Brazilian Cerrado, in carbonate and ferruginous lithology, at entrance zones with presence of water bodies in the cavity. Multivariate analysis for abiotic factors indicates the formation of two clusters: the first formed by caves in the Atlantic Forest biome and Atlantic Forest/Caatinga ecotone, in carbonate and marble lithologies, with altitudinal variation from 23m to 246m, inserted in a matrix with vegetal formations (forest, grassland, and savanna) and presence of endemic anurans. The second cluster for abiotic factors is formed by cavities in ferruginous, quartzitic, and granitic lithologies, with presence of forest landscape matrix, grassland, and rocky outcrops with perennial water; this scenario is inhabited by Bokermannohyla martinsi (restricted to the Quadrilátero Ferrífero region) and Ischnocnema manezinho endemic to Santa Catarina. Categorical variables for biological factors showed groupings with antagonistic characteristics: one group characterized by animals with restricted distribution area, endemics and rare or infrequent in the local herpetological community; diurnal period; cryptic habits; reproduction sites in caves, burrows, or river/stream or forest floor; and "endangered - EN" conservation status according to IUCN. The second group consists of anurans with wide and moderate distribution areas, without endemism and common in the environment; nocturnal animals; arboreal habits; open habitat; reproduction sites in marshes/lakes and river backwaters; without conservation threat status. We also present a previously unreported predation event of an anuran Crossodactylus caramaschii by a fishing spider (Trechaleoides biocellata) inside a cave in São Paulo State, supporting the scientific framework of anuran interaction with the subterranean community.
Anurofauna and neotropical caves: biotic and abiotic factors that modulate the occupation of underground habitat
Keywords: Diversidade anurofaunística; Lacuna Linneana; Lacuna Wallaceana; Ocupação de habitat; Anuran diversity; Habitat occupancy; Linnean gap; Wallacean gap; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA